Antibacterial Activity of Juglans regia L. Dry Husk Extract against Streptococcus mutans and Lactobacillus: An In Vitro Study - Ola Hameed Turki; Zainab Juma Jafar (Wolters Kluwer Medknow Publications, 2023)
Introduction: We aimed to evaluate the anti-bacterial effect of the Juglans regia dry husk ethanolic extract against Streptococcus mutans and Lactobacillus. Methods: A quantity of 200 g of dry husk was ground into powder and sieved until no large particles were found, then mixed with 1 L of 70% ethanol, yielding 20 g of J. regia paste after ethanol exclusion by vacuum evaporator and lyophilization. The Agar well diffusion method was used to detect the antibacterial activity. Statistical analysis was carried out using Welch's t-test (unequal variances t-test) via R software. Results: The J. regia dry husk extract showed statistically significant higher bacterial growth inhibition in comparison with prophylaxis pumice paste for both S. mutans and Lactobacillus. Conclusion: Ethanolic dry husk extract has antibacterial activity against both S. mutans and Lactobacillus.